FORMULATION AND TEST OF ANTIOXIDANT ACTIVITY OF TEA BAG COMBINATION OF BLACK (Camellia sinensis OKvar. assamica (Mast)) AND MANALAGI APPLE (Malus sylvestris (L.) Mill.) - Setyani, Indrawati Kurnia; Prasdiantika, Ricka (Pusat Unggulan IPTEK Poltekkes Kemenkes Malang, 2025)
Abstract: Tea bags are a single dry tea product or a mixture of several types of tea or with the addition of other food ingredients that are permitted according to applicable regulations and are packaged and ready to be brewed. This research created a tea bag formulation from black tea (Camellia sinensis OK var. assamica (Mast)) and manalagi apple (Malus sylvestris (L.) Mill.) which has specific properties, namely antioxidants with a ratio of F1 (25:75), F2(50:50), and F3(75:25). This research aims to determine the quality test and antioxidant activity of tea bags combining black tea and manalagi apples. This research uses a quantitative descriptive method with parameters including organoleptic tests, water content, ash content and antioxidant activity. The organoleptic results of the tea bag have a brown tea color, smell typical of tea and taste bitter, slightly sweet. The water content test results for F1, F2, and F3 were respectively 5.426%; 4.476%; 3.686 %. The ash content test results for F1, F2, and F3 respectively were 3.611%; 5.537 %; 6.507 %. The quality test results are in accordance with SNI standards. The IC50 value of tea bag preparations in F1, F2, and F3 respectively was 61.91 ppm; 84.21 ppm; and 96.43 ppm. F1 has the strongest antioxidant activity due to the addition of more manalagi apples. The results showed that the antioxidant activity of the black tea and manalagi apple formulations was included in the strong category.